A Comparative Study of Laparoscopic Vs. Open Hernia Repair: Outcomes and Patient Satisfaction - Dr. Milindkumar Kadu Wankhede; Dr. Gaurav Arvind Kolte; Dr. Alka Rajendra Patil; Dr. Anilkumar Bhaskar Patil; Dr. Yogesh Pralhad Chaudhari (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Hernia repair is one of the most common surgical procedures worldwide, with various techniques employed to optimize patient outcomes and satisfaction. This study aims to compare the outcomes and patient satisfaction between laparoscopic and open hernia repair techniques. Methods: This retrospective cohort study involved 120 patients who underwent hernia repair at a single tertiary care center, with 60 patients undergoing laparoscopic repair and 60 undergoing open repair. Outcomes measured included postoperative recovery time, recurrence rates, complications, and patient satisfaction regarding cosmetic results and overall treatment experience. Statistical analysis was conducted using Chi-square tests and t-tests where appropriate. Results: The laparoscopic group demonstrated a significantly lower recurrence rate (3.3% vs. 13.3%, p=0.045) and shorter postoperative recovery times in terms of resuming daily activities (3.2 vs. 6.4 days, p<0.001) and returning to work (5.6 vs. 9.2 days, p<0.001). Patients in the laparoscopic group also experienced fewer complications (5% vs. 20%, p=0.008) and reported higher satisfaction with cosmetic outcomes (8.7 vs. 7.2, p<0.001) and overall treatment (8.5 vs. 6.9, p<0.001). The likelihood of recommending the surgery was also higher among the laparoscopic patients (95% vs. 75%, p=0.013). Conclusion: Laparoscopic hernia repair is associated with better clinical outcomes, fewer complications, and higher patient satisfaction compared to open hernia repair. These findings support the adoption of laparoscopic techniques as a preferred option for hernia repair, subject to individual patient conditions and surgical expertise.